Anting Emas di Jungur Babi: Analisa Penggunaan Kiasan terhadap Pola Perkataan Item-Evaluasi Menurut Amsal 11:22 - Aska Aprilano Pattinaja; Hemy Bernard Warikry; Farel Yosua Sualang (LOGON ZOES: Jurnal Teologi, Sosial dan Budaya, 2024)
Proverbs 11:22 is a unique section of Solomon's Proverbs because it contains a metaphor comparing an immoral woman to a gold ring on a pig's jaw. The debate about this verse is the misinterpretation of this verse as anti-feminist or misogynistic, which implies a misunderstanding of the intended context. There is a gap in the previous research which only discusses the study of the meaning and its embelamatical implications, thus not answering the need for a comprehensive explanation of the figurative context and meaning of the verse. Therefore, to provide the correct interpretation and perspective, this research is conducted in discussing the figurative meaning and analyzing the item-evaluation speech pattern, so as to interpret the figurative meaning of "gold ring in a pig's jaw" as the main factor of character building, as well as correcting the wrong understanding of the misinterpretation of Proverbs 11:22, based on the hermeneutical method of wisdom literature, with an intrepetitive design approach.  This study found three things, namely, first, the figurative element, as an insult to people who live immorally. Second, the element of position, where there is a change in the position of status and appreciation as a result of the decision to live without moral ethics because it rejects wisdom. Third, the element of evaluation, which occurs as a form of judgment due to the decision to live immorally and results in the acceptance of social sanctions. These three elements are interrelated and form a pattern of warning and evaluation of life. The results found are a warning for everyone to act carefully in moral ethics that come from wisdom. Amsal 11:22 merupakan bagian amsal Salomo yang unik karena mengandung kiasan yang menyamakan wanita yang tidak susila dengan cincin emas di jungur babi. Perdebatan yang muncul dalam ayat ini adalah kesalahan penafsiran ayat ini sebagai anti feminim atau misoginis, yang berimplikasi pada pemahaman keliru tentang konteks yang dimaksud. Terdapat kesenjangan penelitian sebelumnya yang hanya membahas kajian makna dan implikasi embelamatiknya sehingga tidak menjawab kebutuhan penjelasan konteks kiasan dan makna ayat secara komprehensif. Oleh sebab itu untuk memberikan interpretasi dan perspektif yang tepat, maka penelitian ini di lakukan dalam membahas makna kiasan dan analisa pola perkataan item-evaluasi, sehingga dapat mengartikan makna kiasan “cincin emas di jungur babi” sebagai faktor utama pembentukan karakter sekaligus meluruskan pemahaman yang keliru atas kesalahan penafsiran dari Amsal 11:22, berdasarkan metode hermeneutika sastra hikmat, dengan pendekatan intrepetative design.  Penelitian ini menemukan tiga hal, yakni pertama, elemen perkataan kiasan, sebagai hinaan bagi orang yang hidup asusila. Kedua, elemen posisi, dimana terjadinya perubahan posisi status dan penghargaan sebagai akibat keputusan untuk hidup tanpa etika moral karena menolak kebijaksanaan (hikmat). Ketiga, elemen evaluasi, yang terjadi sebagai bentuk penilaian akibat keputusan hidup asusila, dan berakibat penerimaan sanksi sosial. Ketiga elemen ini saling berkaitan, yang membentuk pola peringatan dan evaluasi hidup. Hasil yang ditemukan menjadi peringatan bagi semua orang agar bertindak dengan hati-hati dalam etika moral yang bersumber dari kebijaksanaan (hikmat).